Some thoughts on civil engineering study programmes/Mintys apie statybos krypties studijų programas - Čižas, Algirdas E. (Journal of Civil Engineering and Management, 1999)
More than four hundred study programmes are registered in Lithuanian higher education institutions for undergraduate level, and the same number for postgraduate studies. Any demand of a labour market cannot substantiate such an abundance of programmes. Some details of the previous mechanism of financing universities had stipulated the increase of the number. Sickness of the abundance is characteristic of the civil engineering subject area as well. In Table 1 there are listed all the programmes in this subject area: 12 different programmes for undergraduate, 10 for Master, and 5 for specialised professional studies. Some very specialised names of programmes make us suppose the programmes are for non-university studies. Basic (undergraduate), Master and Doctoral studies make a consistent system of Lithuanian civil engineering higher education. Specialised one-year professional postgraduate study programmes do not fit to the system, they have been provoked by a wrong image of inferiority of undergraduate programmes. Similar subjects are included into both undergraduate and “professional” study programmes (examples are presented in Table 2). The title of Dipl Eng could be justified if it would be awarded by any professional body, not by universities. If it is necessary to lengthen duration of civil engineering education, it is better to substitute the four-year undergraduate programmes for five-year ones. Binary higher education system is coming to Lithuania, non-university study programmes and higher education institutions (colleges) will be introduced. Civil engineering study programmes fitting for this new higher education sector should be selected. Almost all the civil engineering programmes consist of very small courses (mostly of two-three credits), and six-seven subjects are studied every term. It is reasonable to shorten the term list up to five subjects, not more. Some efforts of civil engineers are directed to creating a common European higher education area according to the Sorbonne and Bologna declarations [3, 4]. The European Union Civil Engineering Education and Training Thematic Network Project (EUCEET) has a task to elaborate common requirements of curriculum, quality assessment and mutual recognition of the higher education.Article in Lithuanian.First Published Online: 26 Jul 2012